SERANGAN HAMA PUTIH PALSU Cnaphalocrosis medinalis GUENEE. PADA TANAMAN PADI SAWAH DI KECAMATAN RANOYAPO KABUPATEN MINAHASA SELATAN - Vera E. Tangkilisan; Christina L. Salaki; Moulwy F. Dien; Elisabet R.M. Meray (COCOS, 2014)
ABSTRACTThe study aims to determine the pest Cnaphalocrosis medinalis on rice crops in the vegetative phase Ranoyapo districts, South Minahasa Regency. The study uses a survey method in 4 locations / villages in the district Ranoyapo: Ranoyapo Village, West PoopoVillage, North Poopo Village, and MopoloVillage. Each location/village rice fields specified 3 (replicates) as the observation and sampling. Sampling was conducted on each diagonal fields. In each sub-plot clumps of rice as determined 5 sampling sites. Implementation of sampling vegetative phase in rice plants once a week for 6 weeks. The results showed that C. medinalis Ranoyapo has spread in the district with the highest attack found in Ranoyapo village location reached 18.66 %, after reaching West Poopo 8.07%, North Poopo reached 4.29% and Mopolo reached 4.07 %. C. medinalis highest percentage of attacks found in plants aged 6 weeks after planting (mst) which reached 20.66 % , then 5 mst old plants reached 13.55 % , 4 mst old plants reached 10.88 % , and the plant was 3 mst reached 7.55% , while the old plants 1 and 2 mst not encountered attacks. The highest population of C. medinalis found in location for Ranoyapo village reaching an average of 12.7 tail , then the village of West Poopo 4.3 tails , North Poopo Village 3.5 tail , and the tail 3.2 Mopolo village.Key words : Cnaphalocrosis medinalis, Rice field